LEGAL PROTECTION FOR CREDITORS WITH FIDUCIARY COLLATERAL - Romli Arsad (INFOKUM, 2023)
The purpose of this research is to see the legal protection for creditors at PT. People's Credit Bank "Karyajatnika Sadaya" which has received fiduciary guarantees, as well as what legal remedies the creditor has if the debtor defaults. Empirical legal studies fall into this category. This study uses primary and secondary data as data sources. The method used in this study is the juridical-sociological method. Information collected through literature study was then examined qualitatively. The results in this study are legal protection for creditors with fiduciary guarantees at PT. BPR Karyajatnika Sadaya if the debtor defaults and is given special rights over his receivables based on the Fiduciary Guarantee Law. Then in accordance with the provisions of Article 21 paragraph (4) of the Fiduciary Law, the results of the transfer and/or claims that arise become a substitute fiduciary object from the fiduciary object transferred by law. The fiduciary receiving party, in this case the creditor, can file a lawsuit against the fiduciary giving party to fulfill its obligations if the goods or objects used as the object of the fiduciary guarantee are not available or are not available according to what is stated in the attachment. As well as the legal actions of creditors for default debtors handled by the company as part of the dispute resolution process. If the debtor still does not want to fulfill it, the creditor can take additional actions, including through non-litigation and litigation channels, after first issuing a warning in the form of a warning and a warning letter.